Prescriber Continuity and Disease Control of Older Adults - Maciejewski, Matthew L. (Med Care, 2017)
BACKGROUND: Medicare beneficiaries with multiple chronic conditions (MCCs) are typically seen by multiple providers, particularly specialists. Clinically appropriate referrals to multiple specialists may compromise the continuity of care for MCC beneficiaries and create care plans that patients may find challenging to reconcile, which may impact patient outcomes. OBJECTIVE: To examine whether glycemic control or lipid control was associated with the number of prescribers of cardiometabolic medications. RESEARCH DESIGN, SUBJECTS AND MEASURES: A retrospective cross-sectional cohort analysis of 51,879 elderly Medicare FFS beneficiaries with diabetes and 129,762 beneficiaries with dyslipidemia living in 10 east coast states. Glycemic control was defined as having an HbA1c<7.5. Lipid control was defined as an LDL<100 for beneficiaries with heart disease or diabetes or an LDL<130 for all other beneficiaries. We examined the association between the number of prescribers of cardiometabolic medications and disease or lipid control in 2011 via logistic regression, controlling for age, gender, race, Medicaid enrollment, 17 chronic conditions and state fixed effects. RESULTS: Among beneficiaries with diabetes, 76% with one prescriber had well controlled diabetes in 2011, which decreased to 65% for beneficiaries with 5+ prescribers. In adjusted analyses, Medicare beneficiaries with three or more prescribers were less likely to have glycemic control than beneficiaries with a single prescriber. Among those with dyslipidemia, nearly all (91–92%) beneficiaries had lipid control. After adjustment for demographics and comorbidity burden, beneficiaries with three prescribers were less likely to have lipid control than beneficiaries with a single prescriber. CONCLUSIONS: Multiple prescribers were associated with worse disease control, possibly because patients with more severe diabetes or dyslipidemia have multiple prescribers or because care fragmentation is associated with worse disease control.